Measures of healthcare decision-making ability in cognitive aging: a scoping review from the Advancing Reliable Measurement in Cognitive Aging and Decision-Making Ability (ARMCADA) research initiative - Mather, Molly A.; Ece, Berivan; Karpouzian-Rogers, Tatiana; Ho, Emily H.; Bucko, Patricia; Dworak, Elizabeth M.; Novack, Miriam A.; Pila, Sarah; Hosseinian, Zahra; Hanmer, Janel; Gershon, Richard C.; Weintraub, Sandra (Frontiers in Public Health, 2025)
IntroductionDeclines in decision-making (DM) ability are often observed with increasing age and pose significant risk for negative health, financial, and functional outcomes. The Advancing Reliable Measurement in Cognitive Aging and Decision-making Ability (ARMCADA) research initiative aims to improve measurement of DM ability in aging to facilitate early detection of cognitive and functional decline. This scoping review summarizes the extant literature on DM measures in aging, focusing specifically on measures relevant to healthcare decision-making (HCDM).MethodsWe identified articles published between 2018 and 2023 using keywords related to DM abilities in aging populations. Titles and abstracts were first reviewed by two trained reviewers, followed by full-text review and extraction. Results of the current scoping review are reported in adherence to PRISMA-ScR guidelines.ResultsThe scoping review identified 16,286 articles across multiple domains of decision-making, 705 of which met criteria for extraction, and 246 of which were related to healthcare decision-making. There were 86 unique measures across these articles, and 18 of these measures directly targeted decision-making ability. Most measures were administered to clinical groups in English and in-person with a trained examiner. Measures of healthcare DM ability tended to consist of semi-structured interviews or performance-based items, though there were also several self-report measures.DiscussionThe most commonly used measures to assess HCDM ability require trained administration of a semi-structured interview to assess ability to reason about health-related scenarios and are often time-intensive. Creation of a streamlined, standardized measure to assess HCDM ability will benefit both research and clinical care for the aging population.